2014
DOI: 10.5539/gjhs.v6n3p213
|View full text |Cite
|
Sign up to set email alerts
|

Patients Discharged Against Medical Advice from a Psychiatric Hospital in Iran: A Prospective Study

Abstract: Aim:Self- discharged patients are at high risk for readmission and ultimately higher cost for care. We intended to find the proportion of patients who leave hospital against medical advice and explore some of their characteristics.Methods:This prospective study of discharge against medical advice was conducted in psychiatric wards of Zare hospital in Iran, 2011. A psychologist recorded some information on a checklist based on the documented information about the patient who wanted to leave against medical advi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
11
2
Order By: Relevance
“…Substance abuse is one of the established personal factors that significantly increases the risk of DAMA [3,6,[21][22][23], particularly in psychiatric patients [24]. However, we found no significant differences in the proportion of substance abuse between cases and controls.…”
Section: Discussioncontrasting
confidence: 64%
“…Substance abuse is one of the established personal factors that significantly increases the risk of DAMA [3,6,[21][22][23], particularly in psychiatric patients [24]. However, we found no significant differences in the proportion of substance abuse between cases and controls.…”
Section: Discussioncontrasting
confidence: 64%
“…DAMA, on the one hand, leads to dire consequences for patients and, on the other hand, has an increased likelihood of the need for readmission, which creates increased costs for patients and the healthcare system. The results of studies conducted in Iran confirmed the high rate of DAMA and readmission due to this issue ( 13 , 23 , 24 ). Investigating the current situation and also being aware of the causes as well as predictor variables can be useful in planning in order to reduce the rate of DAMA, make patients more satisfied, and improve the quality of services.…”
Section: Introductionmentioning
confidence: 52%
“…The readmission of this class of patients is different among countries; the study conducted in Canada has estimated the readmission rates about 10%, while in other countries 24.4% and 3.7% were reported ( 6 , 10 12 ). This rate in the United States was reported 0.8%–2.2% ( 12 ) and in Iran for the psychiatric patients was 3%, and 20% for the emergency sector ( 13 ). DAMA also can increase healthcare costs of patients and the health system up to 56%.…”
Section: Introductionmentioning
confidence: 95%
“…A review of studies from pub med database between 1963 and 2019 using keyword discharge against medical advice revealed that prevalence rates of DAMA, in an inpatient psychiatry based hospital study to be around 39% [7], a prospective study reported 34.4% of DAMA [8] ,some studies found that it was higher among patients with mental illness than patients with other medical problem [9,10]. According to a detailed literature review by Brook M [11] the prevalence of DAMA ranged from 3 to 51 % with an average of 17%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were done to evaluate the predictors of DAMA which were broadly divided into two groups as patient variables and provider variables [11]. Although the findings were variable, younger age group, male sex , lower socioeconomic status, substance abuse, previous history of DAMA, failure to establish a good provider-patient relationship were the most common findings [7,8,13]. Since substance abuse is a common predictor, a study was done to understand why these patients undergo DAMA [14].…”
Section: Introductionmentioning
confidence: 99%